2009
DOI: 10.1080/13576500802362869
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and depression: Evidence from a large population survey

Abstract: Abstract:There is a considerable body of research arguing for an association between psychotic disorders and atypical brain lateralization -the latter usually being indicated by non-righthandedness. By contrast, there has been less attention given to a possible link between handedness and affective disorders and, unlike the case of psychosis, there is no obvious a priori biological reason for such a link. There are very studies of this in normal populations. This paper uses a new large population survey from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…In contrast, genes associated with handedness ontogenesis are involved in diseases affecting the whole body, which supports our findings from GO analyses and the argumentation pointed out by Brandler et al (2013). Among the significantly enriched diseases were many that had been associated with handedness before, specifically depression (Denny, 2009), bipolar disorder (Nowakowska et al, 2008), language and learning disorders (Geschwind and Behan, 1982), anxiety disorders (Logue et al, 2015), attention deficit hyperactivity disorder (Brandler and Paracchini, 2014), and schizophrenia (Hirnstein and Hugdahl, 2014). …”
Section: Discussionsupporting
confidence: 87%
“…In contrast, genes associated with handedness ontogenesis are involved in diseases affecting the whole body, which supports our findings from GO analyses and the argumentation pointed out by Brandler et al (2013). Among the significantly enriched diseases were many that had been associated with handedness before, specifically depression (Denny, 2009), bipolar disorder (Nowakowska et al, 2008), language and learning disorders (Geschwind and Behan, 1982), anxiety disorders (Logue et al, 2015), attention deficit hyperactivity disorder (Brandler and Paracchini, 2014), and schizophrenia (Hirnstein and Hugdahl, 2014). …”
Section: Discussionsupporting
confidence: 87%
“…A study by Denny [31] conducted on a very large population of people from various European countries found that left-handers were significantly more likely to have depressive symptoms than were right handers. Non-right handers, meaning either ambidextrous or left-handed (also referred to as mixed handedness), are more prone than right-handers to suffer from a range of conditions, including schizophrenia [32,33], psychosis [34] and post-traumatic stress disorder [35].…”
Section: Limb Preference and Performancementioning
confidence: 99%
“…One such trait, left-handedness, occurs in 11.1% of the US population (Gilbert & Wysocki, 1992). Left-handedness clusters in familial lineages (McKeever, 2000) and is related to higher rates of depression, schizophrenia and bipolar disorders in adults (Bellani et al, 2010;Denny, 2009;Leask & Crow, 2005;Nowakowska et al, 2008). Studies of left-handedness and psychiatric disorders in childhood are rare, especially in urban populations.…”
mentioning
confidence: 99%